COMPARATIVE STUDIES BETWEEN OPEN AND ENDOSCOPIC CARPAL TUNNEL RELEASE: REVIEW OF ARTICLES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Squeezing the median nerve in the carpal tunnel as it passes through the wrist causes carpal tunnel syndrome (CTS). It strikes more women than men and usually manifests itself in adulthood. Even after a year of treatment without focused therapy, a third of patients may notice an improvement. Though it happens often and has enormous social and health costs, a complete description of CTS did not arrive until after WWII, and the term itself did not emerge until 1953.